Inflammatory events induced by Lys-49 and Asp-49 phospholipases A2 isolated from Bothrops asper snake venom: role of catalytic activity - Zuliani, Juliana Pavan (2005)
The inflammatory events induced in the peritoneal cavity of mice by two PLA2s isolated from Bothrops asper snake venom were investigated. MT-III, an Asp-49 catalytically active enzyme and MT-II, a catalytically inactive Lys-49 variant induced increase in vascular permeability. Inhibition of enzymatic activity of MT-III with p-bromophenacyl bromide reduced this effect. MT-III induced a larger neutrophil infiltrate than MT-II. This activity was significantly reduced after inhibition of catalytic activity. Reduction in the number of neutrophils was observed when antibodies against l-selectin, CD18 or LFA-1 were used, suggesting the involvement of these adhesion molecules in the effects of both PLA2s. There was no effect with antibodies against ICAM-1 and PECAM-1. Increase in the levels of LTB4 and TXA2, as well as of IL-1, IL-6 and TNF-α, were observed in the peritoneal exudates induced by MT-III. MT-II did not enhance levels of eicosanoids but increased those of cytokines. It is concluded that both PLA2s induce inflammatory events in this model. Since MT-III exerts a stronger proinflammatory effect, the enzymatic phospholipid hydrolysis may be relevant for these phenomena. However, the fact that MT-II induced inflammation suggests that molecular regions distinct from the catalytic site elicit inflammatory events perhaps by interacting with specific cell membrane acceptors.